Toward modeling the predictors of managerial career success: does gender matter? - Eddleston,K. A.; Baldridge,David; Veiga,J. F. (Journal of Managerial Psychology, 2004)
Although research has uncovered important predictors of managerial career success, the causal relationships between these predictors has not been fully explored. Accordingly, we propose and test a model that establishes a link between individual differences, salient career-related beliefs, career enhancing outcomes and managerial career success. Using path analysis, we found that education and career impatience directly affected willingness to relocate and perceived marketability, which in turn led to more promotions offered and greater exposure to powerful networks. Finally, the number of promotions offered directly affected management level, which in turn affected compensation level. With respect to gender differences, we found that beliefs regarding the efficacy of mentoring positively influenced a woman's sense of marketability, and like her male counterpart, exposure to powerful networks. However, we also found that for women managers, unlike men, such exposure did not affect the number of promotions they were offered.
Keywords: Management